Pemanfaatan Media Sosial Instagram Oleh Dikmas Lantas Dalam Mewujudkan Kamseltibcar Lantas - Sari, Arum Monita (Police Studies Review, 2020)
The background of this problem appear because the high number of traffic violations cases, undisciplined society that have impact on accidents and the lack of information about Karawang resort police traffic. Carried out an approach with society through counseling by deliver messages using the Instagram application that conducted by Dikmas Lantas. This research aims to find out whether Utilization of Counseling With Instagram as Communication Media by Dikmas Lantas has been carried out properly, and factors that influence the implementation of counseling through Instagram that requires a system or mechanism to facilitate Dikmas Lantas’ duties. Theory used to analyze the focus of the research are management theory and communication theory. The concepts used are consept of utilization, Instagram, Dikmas Lantas, Kamseltibcar Lantas, Social Media, Perkap No. 21 Tahun 2007 Binluh, and Perkap No. 3 Tahun 2015 Polmas. Systematic reseach method is qualitative approach. This type of research is descriptive research. Data sources of this research are primary and secondary data. Data collection techniques are by interview, observation, and document review. Location is in Satuan Lantas in Karawang Resort Resort Police jurisdiction. Validity with triangulation. Data analyze uses Interactive Analysis model. The results of this research found that counseling by using Instagram application that analyzed by sections 8,9 Perkap No. 21 Tahun 2007, 11 poin B Perkap No.3 Tahun 2015, and communication theory. Management functions have not been implemented optimally. The influencing factors are supporting and obstacle factors which are analyzed by management elements. Conclusion from Utilization of social media Instagram by Dikmas Lantas in manifesting Kamseltibcar Lantas has been implemented but not yet optimally. Constructive suggestion comprise suggestion to optimize operational support. Dikmas Lantas should allocate credit budget. And optimize supporting factors implementing Kamseltibcar Lantas counseling through Instagram.